SAT0487 A randomized, blinded, comparator-controlled trial investigating a 4-week course of lyrica in subjects with knee osteoarthritis who exhibit neuropathic pain, compared with a 4-week course of paracetamol. (15th June 2017) - Wright, A; Moss, P; Benson, HA; Will, R; Chowalloor, P
Abstract : Background: Knee osteoarthritis (OA) has been considered the archetypal model of inflammatory or nociceptive pain [1] but it is apparent that people with knee OA may present with different pain phenotypes including some with features of neuropathic pain [2, 3]. Objectives: The aim of the present study was to select people with knee OA who exhibited features of neuropathic pain based on elevated cold pain thresholds (≥15°C) and elevated PainDETECT scores (≥13) and to determine if pregabalin would be more effective in reducing pain and improving function in this cohort than paracetamol. Methods: The study used a double-blind, randomized, comparator-controlled design in participants with knee OA to compare the effectiveness of a standard dose of paracetamol (1000mg qid) with a titrated dose of pregabalin (Lyrica) taken daily over 28 days. A cohort of 90 participants with moderate to severe painful knee OA (Pain rating ≥4/10) who demonstrated features of neuropathic pain were included in the study. Participants were selected from an initial cohort of 271 OA sufferers recruited from the Perth community based on screening of CPT and PainDETECT. Included participants were randomly assigned to receive either a four week course of pregabalin titrated to a maximum dose of 300mg or a four week course of paracetamol (4, 000mg). Participants were assessed at baseline, 14 and 28 Days. They completed the PainDETECT, WOMAC and PQAS questionnaires. Quantitative sensory testing was carried out at three sites (index knee, contralateral knee, ECRB) using standard methods. Cold and heat pain thresholds were tested using a Peltier thermode and pressure pain thresholds were assessed using a digital algometer. Physical function was assessed using three timed locomotor function tests (sit-to-stand, walk, stairs). Results: Participants receiving pregabalin (300mg) exhibited greater reductions in WOMAC Pain scores (P=0.0001) and PainDETECT scores (P=0.0001) at Day 28 compared to the paracetamol group and a greater increase in pressure pain thresholds (reduced tenderness) (P=0.025) at the index knee. There was no significant difference between the groups in cold pain thresholds (P=0.33). Participants in the pregabalin group completed the physical tests more quickly than the paracetamol group (Sit-to-stand p=0.05, walk p=0.001, stairs p=0.05). The pregabalin group also had a significantly increased likelihood of reducing their PainDETECT score below the entry value of 13 compared to the paracetamol group (OR 9.20; P=0.001) but there was no significant difference in the likelihood of reducing their cold pain threshold below the 15°C entry value (OR 2.26; P=0.14). Conclusions: The group receiving pregabalin 300mg showed greater reductions in pain, reduced features of neuropathic pain and reduced tenderness at the affected knee. Further research is warranted to evaluate pregabalin in this specific patient cohort. References: Harden, R.N., et al., J Pain, 2013. 14(3): p. 281–9. Hochman, J.R., et al., Osteoarthritis Cartilage, 2011. 19(6): p. 647–54. Ohtori, S., et al., Yonsei Med J, 2012. 53(4): p. 801–5. Acknowledgements: The investigators thank Ms Lisa Webster for her contribution to the study. Disclosure of Interest: A. Wright Grant/research support from: Pfizer Inc, P. Moss Grant/research support from: Pfizer Inc, H. Benson Grant/research support from: Pfizer Inc, R. Will Grant/research support from: Pfizer Inc, P. Chowalloor: None declared